New bacteriophage typing system for Yersinia enterocolitica, Yersinia kristensenii, Yersinia frederiksenii, and Yersinia intermedia: correlation with serotyping, biotyping, and antibiotic susceptibility. - Baker, P M (1982)
Yersinia enterocolitica is listed as a single species in Bergey's Manual of Determinative Bacteriology, but has recently been split into "true" Y. enterocolitica, Y. kristensenii, Y. intermedia, and Y. frederiksenii. From 48 bacteriophages isolated from raw sewage, 24 were chosen as being the most useful for differentiating strains within the four Yersinia species. The composite set of 24 phages typed 92% of 236 Y. enterocolitica strains, 100% of 16 Y. kristensenii strains, 97% of 29 Y. frederiksenii strains, and 90% of 20 Y. intermedia strains. The most common phage type in any of the groups contained 22% of the strains tested, but most of the phage types contained greater than 5% of the strains. The new typing schema was tested in three outbreaks of Y. enterocolitica, and the results agreed well with serotyping and epidemiological findings. In the same outbreaks, biotyping (API 20E profiles; Analytab Products, Plainview, N.Y.) and antibiograms were less reliable markers and probably should be used only in conjunction with serotyping or phage typing or both. Caution should be used in identifying cultures of Y. frederiksenii and Y. intermedia with the API 20E system, since the tests at 37 degrees C for L-rhamnose and melibiose fermentation are often delayed past 24 h, which is the cut-off point for the final reading in the API system. There were distinct differences in the susceptibilities of Y. enterocolitica and Y. kristensenii to ampicillin, carbenicillin, and cephalothin, which adds further support for classifying the latter as a separate species.